Neurobiology of severe psychiatric disorders – new approaches in the molecular research landscape - Reich-Erkelenz, D.; Schmitt, A.; Gruber, O.; Dechent, P.; Brockmöller, J.; Tzvetkov, M.; Fischer, A.; Bickeböller, H.; Rossner, M.; Nave, K.-A.; Falkai, P.; Schulze, T. G. (Die Psychiatrie, 2012)
Over many years, intensive research into the molecular biological basis of psychosis (schizophrenia, bipolar disorder) has been conducted via complementary approaches of clinical and molecular biological techniques and strategies, be it linkage analyses, candidate gene association studies, pharmacogenetics, neuroimaging, or further neurobiological investigations in post-mortem tissue and animal models for risk factors of the diseases.However, since these approaches could not successfully explain the very heterogeneous disease pattern of schizophrenia or its overlapping spectra with bipolar disorder, we are in the need of a new perspective. Biological psychiatric research has largely focused on cross-sectional data sets without focusing on a phenotype of utmost relevance: the longitudinal course. Large-scale and systematic studies on the genetic and neurobiological underpinnings of the course of psychosis within a framework are lacking. To fill this gap, we are currently establishing such a framework via the DFG funded Clinical Research Group “Genotype-phenotype relationships and neurobiology of the longitudinal course of psychosis”. Here we will establish large cohorts with this phenotype of interest that is longitudinal in nature and also includes information on functional parameters and environmental factors.
Keywords: Schizophrenia; bipolar disorder; genetics; neurobiology; imaging; epigenetics